Surgeon Experience as Predictors of Outcome of Dacryocystorhinostomy Surgery - Limbu, Ben; BK Rasaily, Suresh; Pant , Aasish Raj; Shrestha, Nisha; Bharati, Dev Raj; Pandey, Triptesh Raj; Gurung , Hom Bahadur (Journal of Nepal Health Research Council, 2024)
Background: Dacryocystorhinostomy surgery aims to treat nasolacrimal duct obstruction and are often performed by general ophthalmologists in developing countries. The aim of this study is to estimate the clinical burden, surgeon’s experience, and outcome of dacryocystorhinostomy surgery.Methods: A cross-sectional survey of Nepalese Ophthalmologists registered with the Nepal Ophthalmic Society was conducted after ethical clearance from Nepal Health Research Council. The survey form consisted of a single mail-shot questionnaire information including the age and experience, average case per month, and participant-reported post-operative complications and failures. Data were entered onto Microsoft excel (Microsoft Corp) and analyzed using SPSS 22.0. The data were presented in graphical and tabular format and appropriate statistical tools were employed for the analysis.Results: Out of 300 practicing ophthalmologist, 135 (45%) comprising male 60 (44.4%) and female 75(55.6%) responded to the survey. Majority of respondents were general ophthalmologists (37 ,41.6%) followed by oculoplastic surgeons (27,30.3%) and other subspecialties (25,28.1%). More than 70% respondents perform 1-10 surgeries /month and only 3% perform >50 surgeries /month. The success rate of 75-90% was reported by 45(50%) respondents whereas > 90% success rate by 41 (46.1%). More than 80% surgeons experienced an infection rate of <1% regardless of the intubation status.Conclusions: This survey revealed huge differences in surgery practice patterns among ophthalmologists in Nepal. The surgical success rate and post-operative infection rate depends upon surgeon experience. Moreover, uniform surgery protocols and training budding ophthalmologists/ young Oculoplastic surgeons in the best modern dacryocystorhinostomy surgery are required. Keywords: Dacryocystorhinostomy; nasolacrimal duct obstruction; oculoplasty; ophthalmologist.